Snake Plant: A Multifunctional Indoor Plant - Gaurav F. Nikam; Sakshi D. Bagade; Sapana T. Yadav; Harshal S. Singh; Christopher B. Lobo; Sanket P. Shinde (Research Perspective on Biological Science Vol. 2, 2025)
Medicinal plants are beneficial for a wide range of ailments. Approximately 25% of all prescription medications are derived from plants, and over three-quarters of the population relies on medicines that come from these medicinal plants. The Dracaena trifasciata Prain, characterized by its snake-like, sharp-edged leaves, is also referred to as “viper’s bowstring hemp” because it serves as a source of plant fibers used in making bowstrings. The study aims to review the multifunctional properties of the snake plant. The name Sansevieria is derived from Duke Raimondo di Sangro, the Prince of Sansevero in Italy. Commonly referred to as the snake plant or mother-in-law’s tongue, there are over 100 species within this genus that originate from tropical regions of Africa. In Chinese culture, the snake plant is regarded as one of the fortunate plants believed to bring good luck, having been cultivated and valued even before the Chinese Ti plant (Dracaena spp.), also known as good luck bamboo. This perennial herb features stiff, decorative leaves. Sansevieria is recognized as the most resilient decorative plant, able to thrive in the least favorable growing conditions. Its hardiness makes it a perfect option for apartment residents who typically struggle with houseplants due to lighting challenges. The snake plant is a timeless and adaptable indoor plant with sword-like foliage. It is great for those who may forget to care for plants and is considered one of the best indoor air purifiers, also known to eliminate significant quantities of benzene, formaldehyde, trichloroethylene, and toluene. Placing Sansevieria trifasciata in an office environment can lower CO2 levels by 10.47% to 19.29%. Dracaena trifasciata Prain is reported to be rich in phytochemicals like phenolic compounds, amino acids, alkaloids, cyanogenic glycosides and organic acids. These bioactive compounds are found in leaves, stems, flowers, fruits and roots of the plants. Moreover, it has demonstrated various pharmacological properties, including analgesic, anti-diarrheal, antioxidant, antimicrobial, and anti-diabetic effects. The air-cleaning benefits of Dracaena trifasciata are discussed in this review. Future research should focus on optimizing the air-purifying capabilities of indoor plants and addressing the drawbacks associated with their use. Use in the interior of the house, at present days some individuals and offices use this plant in interior places for purifying the air. Where some of the present generation people give importance to the oxygen concept. The awareness of the plant by the people is making them adopt the requirements appropriately.